Application of the Law in the Crime of Murder With Premeditation of the Death of Women and Children in the Womb - Sukadana Sukadana; Elza Qorina Pangestika (P3M IAI Nusantara Batang Hari, 2023)
Indonesian positive law, the form of guilt for the crime of taking the life of another person can be intentional and unintentional (negligence). Intentionality is an act that can occur with premeditation or unplanned, but what is important from an event is the existence of